A geometrically nonlinear analysis method for offshore renewable energy systems—Examples of offshore wind and wave devices. (15th April 2022) - Leng, Jun; Wang, Qi; Li, Ye
Abstract: Recently, offshore renewable energy has been experiencing a rapid growth with tremendous demands and a significant challenge of high cost. To reduce the cost, people start to introduce advanced designs such as composite structures and flexible devices. As a consequence, traditional structural dynamic analysis tools are not able to provide a comprehensive analysis for the new designs especially their nonlinearity, which dwarf the development of the offshore renewable technology. In order to facilitate the technology development, we propose a new method to conduct the nonlinear analysis by introducing variable Winkler-type viscoelastic foundation into geometrically exact beam theory. By comparing against commercial tools, the newly proposed method is well validated. Then, applications in wind turbines and wave energy converters are used to demonstrate the advantages of the new methods with detailed analysis. Specifically, structure–soil–wave interaction are studied. For the supporting structure, we found that geometric nonlinearity due to large displacements and elastic couplings caused by composite materials cannot be ignored especially under large loads or for those flexible structures. Furthermore, influences of the damping and the stiffness of the springs on the structural dynamics are analyzed for the flexible wave energy converter. Overall, the flexible features of the present solver also show advantage of meeting the need of simulating different scenarios, and it is expected to serve more designs in relevant areas. Highlights: A numerical method for geometrically nonlinear composite structure is proposed for offshore renewable systems. Structure–soil–wave interaction for offshore wind turbine foundation is extensively studied. Structure dynamics of flexible wave energy converters is analyzed with various scenarios. The results demonstrated that geometric nonlinearity and elastic couplings cannot be ignored for flexible offshore renewable structures.